Exploring the use of english in instagram and its influence on the user’s identity - Nurhantoro, Tri Septa; Wulandari, Novi (LPPM Universitas Mercu Buana Yogyakarta, 2017)
English has been used widely in almost all international forums. In line with the rapid use of social media, in this case Instagram, English is also widely used as the language of self-expression by most of its users, both native and non-native speakers. At least, this is what happened in Indonesia. Most of Indonesian Instagram users, especially youth, use English to write their caption. This phenomenon is important to explore since there is a belief that by actively using a foreign language, it will reduce the sense of nationality within oneself, and even it will lead to the loss of one’s identity. Identity today becomes a very important issue since it shows the sense of belonging of oneself in his/her social interaction. The thing is that the social interaction model in social media is much more complex than the interaction model in the real life. In social media, most of the users do not merely want to show who they really are. They tend to have certain motive on how they can be accepted and appreciated by other users. In other words, they want to be the subject of attention instead of being themselves. Therefore, the concept of identity becomes blurred. Based on the previous description, through the direct observation method, this research aims to seek whether the use of English influences the identity of Indonesian users.